2017
DOI: 10.1002/btpr.2586
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between protein molecules and the virus removal membrane surface: Effects of immunoglobulin G adsorption and conformational changes on filter performance

Abstract: Membrane fouling commonly occurs in all filter types during virus filtration in protein-based biopharmaceutical manufacturing. Mechanisms of decline in virus filter performance due to membrane fouling were investigated using a cellulose-based virus filter as a model membrane. Filter performance was critically dependent on solution conditions; specifically, ionic strength. To understand the interaction between immunoglobulin G (IgG) and cellulose, sensors coated with cellulose were fabricated for surface plasmo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 48 publications
1
13
0
Order By: Relevance
“…Bands in the range of the cytokines molecular weights are observable in the sample washing, meaning that an abundant part of proteins did not pass through the pores of the filter remaining loosely attached to it. By evaluating the total amount of recovered proteins in the various fractions, and also considering the non-passing volume, it appears evident an important loss of cytokines, most probably due to the interactions and binding with the filter membrane, as already observed in other studies [25]. To further confirm the observations revealed by digital electrophoresis, assessing the specific recovery of every protein, the same samples were run on multiplex immunoassays for cytokine detection.…”
Section: Cytokine Recoverymentioning
confidence: 61%
“…Bands in the range of the cytokines molecular weights are observable in the sample washing, meaning that an abundant part of proteins did not pass through the pores of the filter remaining loosely attached to it. By evaluating the total amount of recovered proteins in the various fractions, and also considering the non-passing volume, it appears evident an important loss of cytokines, most probably due to the interactions and binding with the filter membrane, as already observed in other studies [25]. To further confirm the observations revealed by digital electrophoresis, assessing the specific recovery of every protein, the same samples were run on multiplex immunoassays for cytokine detection.…”
Section: Cytokine Recoverymentioning
confidence: 61%
“…It is known that membrane fouling occurs during virus filtration. Hamamoto et al investigated the mechanisms of decline in virus filter performance due to membrane fouling using Planova 20N (Hamamoto et al 2018 ). Their analysis showed that the primary cause of flux decline appeared to be irreversible IgG adsorption on the surface of the virus filter membrane.…”
Section: Development Of Planovamentioning
confidence: 99%
“…Zhou et al [62] applied QCM-D together with SPR and surface acoustic wave to study the adsorption of human immunoglobulin G onto hydrophobized surfaces. Also the adsorption of human immunoglobulin G onto cellulose based membranes for virus removal has been studied by the combination of QCM-D and SPR [116]. Mierczynska-Vasilev et al [102] combined QCM-D with AFM to investigate the adsorption behavior of the constituents of white, rosé and red wine on functional plasma-polymerized coatings.…”
Section: Quartz Crystal Microbalance With Dissipationmentioning
confidence: 99%